ANALISIS PENGUKURAN KINERJA DENGAN MENGGUNAKAN PENDEKATAN BALANCED SCORECARD PADA RSUD DR. SOEDONO MADIUN - Brilian Pamuncak Prasetyo; Wiwik Hidajah Ekowati (Jurnal Ilmiah Mahasiswa FEB, 2015)
The purpose of this study was to measure the performance of Hospital Dr. Soedono Madiun using the Balanced Scorecard approach. This study uses secondary data from the hospital in 2012-2014 and interviews to obtain the necessary data. Balanced Scorecard approach uses four perspectives in the measurement, namely financial perspective, customer perspective, internal business processes, and learning and growth perspective.The study concluded that the performance of Hospital Dr. Soedono Madiun were measured using the Balanced Scorecard approach as a whole can be said to be "sufficient". It can be shown from the analysis of each perspective of the Balanced Scorecard. Hospital Dr. Soedono Madiun can use the Balanced Scorecard approach as an alternative measurement tool for measuring performance.   Keywords: Performance Measurement, Balanced Scorecard, Public Sector, Hospitals